Comprehensive analysis of structural variants in chickens using PacBio sequencing - Zhang, Jinxin; Nie, Changsheng; Li, Xinghua; Zhao, Xiurong; Jia, Yaxiong; Han, Jianlin; Chen, Yu; Wang, Liang; Lv, Xueze; Yang, Weifang; Li, Kaiyang; Zhang, Jianwei; et al. (Frontiers in Genetics, 2022)
Structural variants (SVs) are one of the main sources of genetic variants and have a greater impact on phenotype evolution, disease susceptibility, and environmental adaptations than single nucleotide polymorphisms (SNPs). However, SVs remain challenging to accurately type, with several detection methods showing different limitations. Here, we explored SVs from 10 different chickens using PacBio technology and detected 49,501 high-confidence SVs. The results showed that the PacBio long-read detected more SVs than Illumina short-read technology genomes owing to some SV sites on chromosomes, which are related to chicken growth and development. During chicken domestication, some SVs beneficial to the breed or without any effect on the genomic function of the breed were retained, whereas deleterious SVs were generally eliminated. This study could facilitate the analysis of the genetic characteristics of different chickens and provide a better understanding of their phenotypic characteristics at the SV level, based on the long-read sequencing method. This study enriches our knowledge of SVs in chickens and improves our understanding of chicken genomic diversity.